Physical and Chemical Properties of 4 Years Petai Belalang (Leuca`ena leucocephala) Wood - Yuziah Mohd Yunus, Nor; Mohd Nazri Wan Abdul Rahman, Wan; Razali, Zulhilmi (International Journal of Engineering and Technology, 2018)
The physical and chemical properties are important factors that influence the workability of a material. The main objective of the study is to determine the physical and chemical properties of Petai Belalang (Leucaena leucocephala) with diameter at breast height ranging between 35cm to 41cm. Petai Belalang trees were cut into three height portions (bottom, middle and top). Samples for physical properties were taken from each height portion. Samples for chemical determination came from the bottom, middle and top portion of the trees. The highest specific gravity of Petai Belalang was found at the bottom portion, followed by middle and top portion. Percentage of moisture content increased from bottom to top portion. Tree portion affected the cold water and hot water soluble, alkali solubility, alcohol toluene soluble, ash content and lignin content.
Keywords: Petai Belalang; Leucaena leucocephala; physical properties; chemical properties; tree portion